ECONOMICS OF MILK PRODUCTION OF CATTLE IN GARO HILLS OF MEGHALAYA - SANGMA, ANINDITA D.; MISHRA, B. K. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTThe Garo Hills of Meghalaya was selected for the present study with theobjective to work out the net returns from milk production of different breeds.Altogether 200 farmers were selected for the present study. Out of this, 142, 31,24 and 3 farmers were rearing local cattle calving annually (Group-I), local cattlecalving alternate year (Group-II), cross bred cattle (Group-III) and both breeds(Group-IV) were selected respectively by stratified random sampling technique.The average daily milk yield per milch cow per day was 0.34, 0.30, 9.48 and3.34 litres group I, II, III and IV respectively. The average net returns werenegative for both non-descript local cattle breeds (-Rs. 0.13 and -Rs. 4.48), andhighest for crossbred with Rs. 247.41 per milch cow per day followed by thefarmers having both breeds (Rs. 65.51)Keywords: Milk Production, non-descript local cattle, Net Returns.